CONSIDERATIONS ABOUT TECHNICAL APPLICATIONS OF BIMOBILE MANIPULATORS - Iosif TEMPEA; Diana Nicoleta MILOSTEANU; Marin NEACSA (Fiabilitate şi Durabilitate)
Among the bi-mobile mechanical planar systems, the five element mechanisms are largely applicable, used either as trolley of the electrical drive vehicles, or as machines for reproducing some drawings at the wanted scale or for copying some profiles in the field of machine –tools. The developing of the parallel manipulators lead to the five-element mechanisms to be included in this category, which resulted into extending the applicability of these systems in robotics. A study regarding the fields of usage and proficiency of the assimilation and exploitation of the bi-mobile manipulators in technique is presented in the paper.